Perspectives from the Inaugural “Spinal CSF Leak: Bridging the Gap” Conference: A Convergence of Clinical and Patient Expertise - Callen, Andrew L.; Pisani Petrucci, Samantha L.; Lennarson, Peter; Birlea, Marius; MacKenzie, Jennifer; Buchanan, Andrea J.; the “Spinal CSF Leak: Bridging the Gap” Study Group (American Journal of Neuroradiology, 2024)
BACKGROUND AND PURPOSE: The inaugural “Spinal CSF Leak: Bridging the Gap” Conference was organized to address the complexities of diagnosing and treating spinal CSF leaks. This event aimed to converge the perspectives of clinicians, researchers, and patients with a patient-centered focus to explore the intricacies of spinal CSF leaks across 3 main domains: diagnosis, treatment, and aftercare.MATERIALS AND METHODS: Physician and patient speakers were invited to discuss the varied clinical presentations and diagnostic challenges of spinal CSF leaks, which often lead to misdiagnosis or delayed treatment. Patient narratives were interwoven with discussions on advanced radiologic techniques and clinical assessments. Treatment-focused sessions highlighted patient experiences with various therapeutic options, including epidural blood patches, surgical interventions, and percutaneous and endovascular therapies. The intricacies of immediate and long-term postprocedural management were explored.RESULTS: Key outcomes from the conference included the recognition of the need for increased access to specialized CSF leak care for patients and heightened awareness among health care providers, especially for atypical symptoms and presentations. Discussions underscored the variability in individual treatment responses and the necessity for personalized diagnostic and treatment algorithms. Postprocedural challenges such as managing incomplete symptom relief and rebound intracranial hypertension were also addressed, emphasizing the need for effective patient monitoring and follow-up care infrastructures.CONCLUSIONS: The conference highlighted the need for adaptable diagnostic protocols, collaborative multidisciplinary care, and enhanced patient support. These elements are vital for improving the recognition, diagnosis, and management of spinal CSF leaks, thereby optimizing patient outcomes and quality of life. The event established a foundation for future advancements in spinal CSF leak management, advocating for a patient-centered model that harmonizes procedural expertise with an in-depth understanding of patient experiences.CTDconnective tissue disordersCTMCT myelographyCVFCSF-venous fistulaDSMdigital subtraction myelographyPDPHpost-dural puncture headachePOTSpostural orthostatic tachycardia syndromeRIHrebound intracranial hypertensionSCSFLspinal CSF leak